PERAN MAJLIS TA'LIM RAUDHATUL HIDAYAH FISABILILLAH TERHADAP PERKEMBANGAN KARAKTERISTIK REMAJA - Adista, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
The raudhatul hidayah fisabilillah ta'lim assembly has an important role in improving the character development of teenagers. This research aims to dig deeper into the role of the ta'lim assembly in forming quality adolescent characters. The research method used is qualitative with a case study approach. Data is collected through observation. The research results show that the Ta'lim Raudhatul Hidayah Fisabilillah Council has a significant role in improving the character development of adolescents. The ta'lim assembly provides holistic Islamic religious education, including morals, worship and understanding of the book. Apart from that, the ta'lim assembly also provides space for teenagers to interact and discuss Islamic values, thereby forming good social character. In conclusion, the Raudhatul Hidayah Fisabilillah Ta'lim Council plays an important role in forming quality teenage characters. Therefore, there needs to be attention and support from various parties to increase the role of the ta'lim assembly in forming the character of teenagers in accordance with Islamic teachings.